Chaenothecopsis quintralis, a new species of calicioid fungus - Messuti, Maria Ines (2012)
Chaenothecopsis quintralis from south-western Argentina, is described and illustrated as a new species in the family Mycocaliciaceae. It has been found in three localities in the Andean Patagonian temperate forests, growing strictly on dung of an endemic marsupial Dromiciops gliroides. The new species is distinguished by the hemispheric and black capitulum of ascoma, the presence of asci with croziers, 1-celled brown ascospores, and its fimicolous habitat. Analysis of partial nuclear large subunit rDNA (LSU) sequences showed that this taxon is within Mycocaliciales.